2009
DOI: 10.1177/1090198109338916
|View full text |Cite
|
Sign up to set email alerts
|

Social and Cultural Meanings of Self-Efficacy

Abstract: This article describes the influences of social context on women's health behavior through illustration of the powerful influences of social capital (the benefits and challenges that accrue from participation in social networks and groups) on experiences and perceptions of self-efficacy. The authors conducted inductive interviews with Latino and Filipino academics and social service providers and with U.S.-born and immigrant Latinas and Filipinas to explore direct and indirect influences of social context on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 37 publications
(70 reference statements)
6
83
0
1
Order By: Relevance
“…These results suggest that enhancing women's self-efficacy may increase individual abilities to overcome physical as well as psychological obstacles to be encountered on scheduled screening mammography. (Burke et al, 2009;Molina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that enhancing women's self-efficacy may increase individual abilities to overcome physical as well as psychological obstacles to be encountered on scheduled screening mammography. (Burke et al, 2009;Molina et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The previous research among nonadherent women has suggested the relationship between cognitions regarding the perceived barriers and repeat of mammography, (Ajzen, 2005;Burke et al, 2009;Gierisch et al, 2010b) and also having intention to maintain mammogram adherence (O'Neill et al, 2008). While both intervention groups received similar education programs regarding the barriers of getting mammography, perceived :http://dx.doi.org/10.7314/APJCP.2014.15.17.7309 Mammography Screening among Iranian Women barriers did not satisfy the criteria for mediation in the TPB intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Selfefficacy does not explain how it emerges and differs in social contexts (Burke et al, 2009b). On the contrary, the Bourdieusian perspective sees "cultural accessibility and capital" (a power dimension) as an antecedent of self-efficacy (Bandura, 1993: 142).…”
Section: Differentiating the Bourdieusian Approach From Tpb And Self-mentioning
confidence: 99%
“…But, eventually, any self-efficacy will be predirected to habitus-corresponding fields (doxa). Recent research tries to align selfefficacy and social context (Boardman & Robert, 2000;Burke et al, 2009b;Kiilo & Kutsar, 2012), expressing the hope that if it can be demonstrated that self-efficacy is dependent, to some degree, on the location of an individual in the broader macrosocial order, then self-efficacy may provide a conceptual bridge between structure and agency (Boardman & Robert, 2000, 119).…”
Section: Differentiating the Bourdieusian Approach From Tpb And Self-mentioning
confidence: 99%
“…Burke et al (20) found that when analyzed within the domain of social capital (benefits from participation in social networks and groups, dependent on one's social position) perceived self-efficacy had meanings more varied and complex than those reflected in SCT. These meanings-linked to caring, support, relationships, and family and defined by connections with others that enable women to take care of those most important to themwere shaped by institutional, family, and community spheres.…”
Section: Wwwannualreviewsorg • Breast Cancer Screening Promotionmentioning
confidence: 99%